Exercise self-efficacy is weakly related to engagement in physical activity in persons with long-standing spinal cord injury. Issue 20 (24th September 2020) - Kooijmans, Hedwig; Post, Marcel; Motazedi, Ehsan; Spijkerman, Dorien; Bongers-Janssen, Helma; Stam, Henk; Bussman, Hans
Abstract: Aims: Many people with a long-standing spinal cord injury have an inactive lifestyle. Although exercise self-efficacy is considered a key determinant of engaging in exercise, the relationship between exercise self-efficacy and physical activity remains unclear. Therefore, this study examines the relationship between exercise self-efficacy and the amount of physical activity in persons with long-standing spinal cord injury. Methods: This cross-sectional study included 268 individuals (aged 28–65 years) with spinal cord injury ≥ 10 years and using a wheelchair. Physical activity was measured with the Physical Activity Scale for Individuals with Physical Disabilities. Exercise self-efficacy was assessed with the Spinal cord injury Exercise Self-Efficacy Scale. Univariate and multivariable regression analyses were performed to test for the association between exercise self-efficacy and physical activity, controlling for supposed confounders. Results: Univariate regression analysis revealed that exercise self-efficacy was significantly related to the level of daily physical activity (β = 0.05; 95% CI 0.04–0.07; 15% explained variance; p  < 0.001). In multivariable regression analysis exercise self-efficacy remained, explaining a significant additional amount of the variance (2%; p  < 0.001) of physical activity. Conclusion: Exercise-self efficacy is a weak but independent explanatory factor of the level of physical activity among persons with long-standing spinal cord injury. Longitudinal trials are needed to study the impact of interventions targeting an increase of exercise self-efficacy on the amount of physical activity performed. Implications for rehabilitation: Pre-intervention levels of exercise-self-efficacy might mediate the effectiveness of interventions that aim at increasing physical activities in people with a long-standing spinal cord injury. Enhancing exercise-self efficacy may improve levels of physical activity, even in people with a long-standing spinal cord injury. When it comes to enhancing physical activity, efforts to enhance non-structured daily physical activities such as household activities and gardening might be as important as efforts to enhance sports and other physical exercise.